The Effect of Intrinsic Rewards and Extrinsic Rewards on Performance with Job Satisfaction as Intervening Variables - Reno Widhi Pramono (Syntax Corporation Indonesia, 2021)
The world is facing a fast global development. It requires businesses to be able to compete in any developments. Companies need to be supported by the good Performance of the employees to achieve the vision and mission of the organization. Rewards and Job Satisfaction are two variables that can influence Performance. Rewards can be either Intrinsic and Extrinsic. If both types of Rewards are high so as to form high Job Satisfaction, then it can impact Performance improvement of employees. Based on this, this research aims to analyze the influence of Intrinsic Rewards and Extrinsic Rewards to Performance with Job Satisfaction as an intervening variable. This research uses a quantitative approach. Data collection techniques used by distributing questionnaires to 52 contract employees division of Corporate Customer Access Network at PT. Telekomunikasi Indonesia, Tbk. Witel Jatim Surabaya. Sampling techniques in this research using census method. Mechanical testing of the data used in this research is SEM-PLS. Results of this research shows that Intrinsic Rewards influence positively and significantly related to Performance, while Extrinsic Rewards influemce negatively and not significantly related to Performance. The next results shows that Job Satisfaction can mediating partially the relationship of Intrinsic Rewards to Performance and mediating fully the relationship of Extrinsic Rewards to Performance.